Art for every home Associated American Artists : 1934-2000 - Seaton, Elizabeth G. 19XX-; Myers, Jane 1955-; Windisch, Gail; Condominas, Laura Duke 1951- (Marianna Kistler Beach Museum of Art, Kansas State University, 2015)
"This book will provide the first comprehensive and critical overview of Associated American Artists (AAA), the commercial enterprise best known as the publisher of prints by Thomas Hart Benton, John Steuart Curry, and Grant Wood. It addresses not only AAA's storied involvement in the sale of American prints via mail-order catalogue, but also its ongoing promotion of American art in a range of mediums over six decades. Through aggressive marketing of studio prints, reproductions of art, ceramics and textiles, and associations with corporate advertisers, AAA sought to bring "original" American art over the threshold of every American home"--